2019
DOI: 10.1111/soc4.12718
|View full text |Cite
|
Sign up to set email alerts
|

Populist communication and media environments

Abstract: Populist leaders and movements have long adapted their communication practices to fit their media environments. Yet, research on the relationship between media and populism has been limited until recently. This article offers an overview of how media researchers have been identifying populist media and communication practices and investigating ways in which media structures may constrain or enable the growth of populist movements. It discusses three different scholarly frameworks that suggest that social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…Research on new information environments (van Aelst et al, 2016) and media regimes (Williams & Delli Carpini, 2011) has become central to our understanding of many defining political communication phenomena in the twenty-first century. This is true for the study of populism (Nadler, 2019), mediatization (Strömbäck & Esser, 2014), and post-truth politics (Waisbord, 2018), among other things. Against the backdrop of the growing range of approaches to examining these new information environments, it seems unfortunate that the once widely cited and influential concept of hyperreality (Baudrillard & Poster, 2001) receives less attention in the newer literature, even though its relevance for the comprehension of contemporary political communication has only increased.…”
Section: Introductionmentioning
confidence: 92%
“…Research on new information environments (van Aelst et al, 2016) and media regimes (Williams & Delli Carpini, 2011) has become central to our understanding of many defining political communication phenomena in the twenty-first century. This is true for the study of populism (Nadler, 2019), mediatization (Strömbäck & Esser, 2014), and post-truth politics (Waisbord, 2018), among other things. Against the backdrop of the growing range of approaches to examining these new information environments, it seems unfortunate that the once widely cited and influential concept of hyperreality (Baudrillard & Poster, 2001) receives less attention in the newer literature, even though its relevance for the comprehension of contemporary political communication has only increased.…”
Section: Introductionmentioning
confidence: 92%
“…22 When it comes to populist actors, they tend to favorably view opportunities offered by narrative-driven politics. 23 To a large extent, this is because the above-discussed media structures demand political communication and culture which are partly in tune with those practiced by populists. 24 For instance, as populists tend to discursively oppose themselves to the mainstream politicians, this is natural for them to also strive for a maximum distance from those politicians' routines and practices, including traditional channels and formats of communication.…”
Section: Rationales: Why Narratives? Why Now?mentioning
confidence: 99%
“…Building upon recent experimental research that showed how recipients' emotions and cognitions are affected by short populist messages, such as electoral posters (Wirz, 2018) or news items (Hameleers et al, 2019;Hameleers et al, 2021), this study extends the discussion through shifting attention to the influence of populist narratives. The need to incorporate populist narratives into analysis is determined by the ongoing changes in political communication culture characterized by mediatization and personalization of politics (Esser & Strömbäck, 2014), the growing range of formats and sources of political communication, and the reduced institutional gatekeeping (Nadler, 2019). These and other related processes contribute to a political environment in which the competition of ideas often gives way to the competition of stories making the questions posed in the previous paragraph especially relevant.…”
mentioning
confidence: 99%
“…The narrative transportation effect (Gerrig, 1993;Green & Brock 2000) is proposed as a proxy for accessing the relative appeal of populist storytelling. It is assumed that political stories framed in a populist way (Nadler, 2019), social networking platforms (Enli & Rosenberg, 2018), mass culture (Holbert et al, 2003), etc.…”
mentioning
confidence: 99%